MDM-2 protein expression in nasopharyngeal carcinomas. Comparative study with p53 protein expression. Issue 6 (December 1995) - Kanavaros, P; Kouvidou, C; Dai, Y; Tzardi, M; Datseris, G; Darivianaki, K; Rontogianni, D; Delides, G
Abstract : Aims —To investigate the immunohistochemical expression of MDM-2 protein in comparison with that of p53 protein in nasopharyngeal carcinomas. Methods —Formalin fixed, paraffin wax embedded tissue from 59 cases of nasopharyngeal carcinoma was stained by immunohistochemistry for MDM-2 and p53 proteins. Results —The tumours were divided histologically into seven cases of keratinising nasopharyngeal carcinoma (KNPC), 14 cases of non-keratinising nasopharyngeal carcinoma (NKNPC), and 38 cases of undifferentiated nasopharyngeal carcinoma (UNPC). MDM-2 nuclear expression was observed in 0/7 KNPC, 1/14 NKNPC, and 11/38 UNPC. p53 nuclear expression was observed in 1/7 KNPC, 2/14 NKNPC, and 15/38 UNPC. Parallel MDM-2 and p53 expression was found in 12 cases (11 UNPC and one NKNPC). Discordant MDM-2-/p53 + expression was found in six cases (four UNPC, one NKNPC, and one KNPC), and absence of expression of both proteins in the remaining 41 cases. Conclusions —Expression of MDM-2 and p53 proteins may be associated with the level of tumour cell differentiation in nasopharyngeal carcinoma. Simultaneous expression of MDM-2/p53 in a proportion of UNPC suggests that MDM-2 protein may be responsible for stabilisation of p53 protein in these cases, in view of the previous demonstration of the p53 gene in germ line configuration. This could be important in the pathogenesis of these cases, since MDM-2 may deregulate the p53 dependent growth suppressive pathway. Discordant MDM-2-/p53 + expression in a few cases of nasopharyngeal carcinoma may reflect stabilisation of p53 protein by other proteins, or p53 mutations unable to activate MDM-2.